2014
DOI: 10.1007/s11101-014-9335-7
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Vietnamese plants for potential anticancer agents

Abstract: Higher plants continue to afford humankind with many new drugs, for a variety of disease types. In this review, recent phytochemical and biological progress is presented for part of a collaborative multi-institutional project directed towards the discovery of new antitumor agents. The specific focus is on bioactive natural products isolated and characterized structurally from tropical plants collected in Vietnam. The plant collection, identification, and processing steps are described, and the natural products… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Likewise, flavnoids are also known intestinal motility and water and electrolyte secretion inhibitors and even they do have antioxidant activity which may have a role in suppressing the catalytic activity of different enzymes including enzymes for the synthesis of prostaglandins [ 22 , 47 ]. Parallel to this fact it is reported that Indigofera spicata do have antioxidant and cytotoxic activity [ 17 , 18 ] that may have a role in its antidiarrheal mechanism of action. Furthermore, steroids may also enhance the absorption of hydroelectrolytes across the intestinal lumen [ 23 , 48 ].…”
Section: Discussionmentioning
confidence: 90%
“…Likewise, flavnoids are also known intestinal motility and water and electrolyte secretion inhibitors and even they do have antioxidant activity which may have a role in suppressing the catalytic activity of different enzymes including enzymes for the synthesis of prostaglandins [ 22 , 47 ]. Parallel to this fact it is reported that Indigofera spicata do have antioxidant and cytotoxic activity [ 17 , 18 ] that may have a role in its antidiarrheal mechanism of action. Furthermore, steroids may also enhance the absorption of hydroelectrolytes across the intestinal lumen [ 23 , 48 ].…”
Section: Discussionmentioning
confidence: 90%
“…The tropical rainforests include many of the 25 biodiversity `hotspots' that cover only 1.4% of the world's surface while containing nearly half of all vascular plant species (36). Our project team has collected plants previously from different tropical rainforests, with the intention of finding new anticancer agents, including in the Dominican Republic (37), Ecuador (37), Indonesia (37), Peru (37), Vietnam (38), and most recently Laos. Access to plant species in foreign countries must be gained through the development of detailed intellectual property agreements as a result of the provisions of the 1992 United Nations Convention on Biological Diversity (39) and the 2010 Nagoya Protocol (40).…”
Section: Collection and Processing Of Organismsmentioning
confidence: 99%
“…Once an appropriate plant-collection agreement with a source country has been mutually signed, the NAPRALERT® database housed at UIC is used to aid in the selection of plant genera found in a given country for which there are relatively few phytochemical reports (38). It is worthwhile collecting more than one plant part from a given plant acquisition ( e.g .…”
Section: Collection and Processing Of Organismsmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Technical progress made by our group program project has appeared in the literature periodically. [12][13][14][15][16] In the present contribution, we focus on recent progress of characterization of anticancer lead compounds from selected higher plants collected in the Dominican Republic, Indonesia, and Vietnam as part of this program project collaboration. The plant species from our work referred to below were collected sustainably by the University of Illinois at Chicago, in accordance with existing international treaty requirements, as explained in detail in a recent book chapter.…”
Section: Introductionmentioning
confidence: 99%